Breaking Stereotypes: An Analysis of Gender-Based Refusal Strategies among Intermediate Indonesian English Language Learners - Dhafid Wahyu Utomo; Novela Francisca Karuniawati; Yusti Fargianti; Ezis Japar Sidik (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aimed to investigate gender-based differences in the use of refusal strategies among 60 intermediate Indonesian English as a Foreign Language (EFL) learners. A qualitative approach was employed using a Discourse Completion Test (DCT) consisting of 12 scenarios. The refusal taxonomy proposed by Beebe et al. (1990) was utilized to analyze the collected data. Findings showed that both male and female participants most frequently used indirect strategies, with females exhibiting a slightly greater range of indirect strategies. Additionally, the interlocutor's status was found to influence the choice of refusal strategies used by participants. However, no significant gender-based differences were observed. The results suggest that EFL learners tend to express refusal in a polite and considerate manner to avoid causing offense. Future studies should consider incorporating diverse data collection instruments to achieve a more comprehensive understanding of pragmatic competency.